KONSELING MULTIKULTURAL: RESILIENSI KELUARGA DITENGAH KERAGAMAN DI INDONESIA - Widaningsih Widaningsih (UIN Kiai Haji Achmad Siddiq Jember, 2022)
The purpose of this study is to examine the relationship with cross cultur counseling as a tool in order to build resilience in the family. This view refers to the diversity that exists in Indonesia must be a good foundation in building family resilience. With this literature study, the author tries to explain through various literature materials that have been collected. The results of this study state that in order to strengthen family resilience, it is very important for every family to have an understanding of cross cultur counseling. Parents in the family environment must be able to provide good learning related to understanding cross cultur counseling in order to understand and accept diversity. This acceptance becomes one of the tools in order to strengthen resilience in the family. Besides that, there are several important points that we can understand together in building and strengthening resilience in the family, namely, the existence of social harmony and harmony, empathy, and not being aggressive. These three things can encourage and strengthen resilience in the family in the midst of so much diversity.